Comparison of the performance of the extreme value type 1 (EV1) and the rayleigh distribution - 493326 Siti Roslindar Yaziz; Abdul Aziz Abdul Ghani; Fakulti Sains (2003)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2003